Endotracheal intubation through the intubating laryngeal mask airway (LMA-Fastrach™): A randomized study of LMA- Fastrach™ wire-reinforced silicone endotracheal tube versus conventional polyvinyl chloride tracheal tube - Megha U Sharma; Satinder Gombar; Kanti K Gombar; Baljit Singh; Nidhi Bhatia (Indian Journal of Anaesthesia, 2013)
Context: A wire-reinforced silicone tube (LMA-Fastrach™ endotracheal tube) is specially designed for tracheal intubation using intubating laryngeal mask airway (ILMA). However, conventional polyvinyl chloride (PVC) tracheal tubes have also been used with ILMA to achieve tracheal intubation successfully. Aim: To evaluate the success of tracheal intubation using the LMA-Fastrach™ tracheal tube versus conventional PVC tracheal tube through ILMA. Settings and Design: Two hundred adult ASA physical status I/II patients, scheduled to undergo elective surgery under general anaesthesia requiring intubation, were randomly allocated into two groups. Methods: The number of attempts, time taken, and manoeuvres employed to accomplish tracheal intubation were compared using conventional PVC tubes (group I) and LMA-Fastrach™ wire-reinforced silicone tubes (group II). Intraoperative haemodynamic changes and evidence of trauma and postoperative incidence of sore throat and hoarseness, were compared between the groups. Statistical Analysis: The data was analyzed using two Student′s t test and Chi-square test for demographics and haemodynamic parameters. Mann Whitney U test was used for comparison of time taken for endotracheal tube insertion. Fisher′s exact test was used to compare postoperative complications. Results: Rate of successful tracheal intubation and haemodynamic variables were comparable between the groups. Time taken for tracheal intubation and manoeuvres required to accomplish successful endotracheal intubation, however, were significantly greater in group I than group II (14.71±6.21 s and 10.04±4.49 s, respectively ( P<0.001), and 28% in group I and 3% in group II, respectively ( P<0.05)). Conclusion: Conventional PVC tube can be safely used for tracheal intubation through the ILMA.